2018
DOI: 10.3892/etm.2018.6193
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid promotes A549 cell apoptosis via regulating the phosphoinositide 3‑kinase/protein kinase B pathway

Abstract: The present study aimed to evaluate the anti-cancer effect of ellagic acid in human non-small cell lung cancer (NSCLC) A549 cells and to reveal the potential underlying mechanism. The effects of ellagic acid on the cell proliferation of A549 cells were determined by MTT assay. Cell cycle and apoptosis were measured with flow cytometry and Annexin V-propidium iodide staining. Western blotting was used to measure the expression levels of the phosphatidylinositol 3-kinase (PI3K)/protein kinas B (Akt) signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Although EA did not reduce total PI3K expression, EA definitely decreased the expression of p-PI3K, reducing activation of the downstream target MMP9. A similar result was also presented in a previous study19, which showed that EA decreased the expression of p-PI3K without down-regulating total PI3K in nonsmall cell lung cancer. In vivo , KLE and AN3CA cells were injected into BALB/c nude mice to simulate a metastatic environment.…”
Section: Discussionsupporting
confidence: 89%
“…Although EA did not reduce total PI3K expression, EA definitely decreased the expression of p-PI3K, reducing activation of the downstream target MMP9. A similar result was also presented in a previous study19, which showed that EA decreased the expression of p-PI3K without down-regulating total PI3K in nonsmall cell lung cancer. In vivo , KLE and AN3CA cells were injected into BALB/c nude mice to simulate a metastatic environment.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the studies showed that ellagic acid reduces PI3K and AKT phosphorylation and also promotes A549 cell apoptosis that is the preferred way of death in cancer treatment. The ability of induction of programmed cell death of ellagic acid can be attributed to the effect of regulating apoptosis-related proteins [5]. Similarly, in this study results it was showed that ultrastructural and morphological changes of A549 cells caused by ellagic acid imply to apoptosis but clear determination of the cell death mode requires investigations with other apoptosis detection methods.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies on cancer research reported the antitumor, antiproliferative, cell cycle suppressing, proapoptotic, anti-metastatic and anti-angiogenic activities on ellagic acid on a variety of cancer cell lines. Despite these biological activities of ellagic acid on human non-small cell lung cancer (A549) has not been known in details yet and remain unclear [5]. Thus, herein it is aimed to investigate the cytotoxic and antiproliferative activities of ellagic acid on human lung cancer in vitro, together with the possible ellagic acidderived alterations in the cell structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PLE was able to counteract H1299 cells migratory and invasive behaviour, reducing MMP-2 and MMP-9 levels [ 74 ]. In the A549 cell line treated with pure EA, inhibition of the PI3K/Akt signalling pathway was identified as a possible molecular mechanism responsible for the antiproliferative potential of this compound [ 75 ].…”
Section: In Vitro and In Vivo Activity Of Ellagic Acid In Differenmentioning
confidence: 99%